The Influence of E-Wallet Usage and Lifestyle on Consumptive Behavior with Self-Control as a Moderating Variable - Sukra, Widia; Asyari; Hesi Eka Puteri; Rini Elvira (Universitas Yudharta Pasuruan, 2025)
Introduction; The purpose of this study was to measure and analyze the influence of e-wallet usage and lifestyle on consumer behavior, with self Discipline as a moderating variable among Muslim millennials in Bukittinggi City. Method; This study was quantitative with a descriptive approach. A sample of 300 respondents, representing Muslim millennials who use e-wallets in Bukittinggi City, was selected. Data collection involved observation and questionnaire distribution. The data were then analyzed using Structural Equation Modeling (SEM) techniques using the SmartPLS application. Results; The study revealed that both e-wallet usage and lifestyle have a positive and significant impact on consumptive behavior among Muslim millennials in Bukittinggi. Additionally, self-discipline was found to significantly weaken the influence of lifestyle on consumptive behavior, while its moderating effect on the relationship between e-wallet usage and consumptive behavior was not significant. Conclusion;Self-discipline, as a form of self-discipline, has a significant moderating effect in weakening the relationship between lifestyle and consumptive behavior among Muslim millennials in Bukittinggi City. However, its moderating effect on the relationship between e-wallet usage and consumptive behavior is not statistically significant.